Electronic Tax Filing System Usage: The Role of Perceived Ease, Usefulness, Trust With Attitude As a Mediator - Melamaulidah Melamaulidah; Bima Cinintya Pratama; Azmi Fitriati; Tiara Pandansari (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
System is an annual tax return information system through electronic or online tax channels determined by the Directorate General of Taxes. This study aims to examine the antecedents of intention to use by considering the influence of perceived ease, usefulness, and trust with attitude as a mediating variable. The population of this study is individual taxpayers who use the e-filing system at the Purwokerto Pratama Tax Service Office. The sample of this study was determined using an accidental sampling technique. The analysis was carried out using Structural Equation Model (SEM) analysis based on components or variance with a Partial Least Square (PLS) approach. The results of this study show that the perceived ease and usefulness have a positive effect on the intention to use the e-filing. The trust variable does not affect the intention to use the e - filing. In addition, this study also proves the role of attitudes in mediating the perceived ease, usefulness, and trust in the intention to use the e - filing.